Persepsi Guru Terhadap Penerapan Sistem Full Day School: Studi Kasus di SMAN 1 Citeureup - Anggraeni, Novi; Rohman, Baeti; Sholichah, Aas Siti (Fakultas Tarbiyah, Institut PTIQ Jakarta, 2020)
This paper discusses the teacher's perception of the application of the full day school system at SMAN 1 Citeureup. This research is motivated by the existence of an innovation in education set by the government about the school day that is full day school. This type of research is a descriptive qualitative research with field research approach. The research data collection techniques using observation, interviews and documentation. The results of this study indicate that (1) Some teachers respond positively to the full day school policy, if the school is able to support all aspects needed by both teachers and students, starting from the concept of managing a full day school learning that is well planned, structured and directed so that it is more effective in carrying out the learning process and the development of adequate facilities and infrastructure (2) teachers' perceptions about the advantages of full day school systems can be a solution for parents who care about the moral crisis that is being experienced by students at this time. Furthermore, as a means of improving the quality of student morals for the better, and to maximize student time to be more useful by developing students 'talents, interests and creativity (3) teachers' perceptions of the weaknesses of full day school lies in the technical implementation in schools, the lack of student socialization with the surrounding environment inadequate places of residence and facilities and infrastructure (4) management of full day school learning in SMAN 1 Citeureup in accordance with PP No. 19 of 2005 concerning National Education Standards which include program planning, implementation and evaluation.